Energy Absorption Capability of Stainless Steel Type 304 and Type 316 - Salwani, Mohd Salleh; Muhammad Aiman, S. (2015)

(untitled)
This study is focusing on analyzing the specific energy absorption base on stainless steel type 316 with thickness of 3 mm and 6 mm and stainless steel 304 with thickness 3 mm. Tensile tests were conducted by using 100 KN load. Result shows that, thicker specimen is capable of absorbing more specific energy. Stainless steel type 316 is also found to better energy absorber due to its high yield strength.